Strategies, Management of Urban Transport and its Solutions, with Sustainable Development Approach (Case Study: Tehran) - Maryam Esmaeili (Journal of Global Pharma Technology, 2017)
Sustainable transport concepts that are always changing the type of fuel and reduce fuel consumption car or use public transportation to the mind.In the meantime, pay attention to issues relating to sustainable development can be explained by causes instability and factors affecting transport in cities with a sustainable approach examined.In addition, it can transport needs and requirements to achieve sustainable urban design and planning presented. But in the meantime, variables such as dimensions of sustainable development and its axis can specify various aspects of this process.Therefore, the aim of the present study provide urban transport management strategies and solutions with a sustainable development approach, the analytical method.To achieve this goal, first to experience the world of transportation was different cities of the world, then transport axes Paydarmvrd was investigated. As well as transport and traffic studies Tehran was assessed, finally, urban transport planning and management strategies and solutions that were presented.The results show that most interest is the urban management policies, teaching and development of traffic culture as the main solution to the traffic problem in Tehran, which will help to urban planning.Keywords: Urban transportation, Transportation management, Sustainable development, Tehran city.